PENGARUH PIJAT COUNTER PRESSURE TERHADAP INTENSITAS NYERI PADA IBU BERSALIN KALA 1 FASE AKTIF DI PUSKESMAS JUMPANDANG BARU MAKASSAR - Muldaniyah Muldaniyah; Arniati Ardi (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2021)
Pain during labor is the pain that is felt in laboring mothers due to uterine contractions which is a physiological process of the human body when facing labor. Giving interventions in the labor process to reduce maternal pain that takes place during the first stage of the active phase of labor is needed, a very effective method in dealing with pain is to provide counter pressure massage action. The purpose of this study was to determine the effect of counter pressure massage on the intensity of pain in pregnant women during the first active phase at the Jumpandang Baru Public Health Center Makassar. This type of research uses quantitative research with a quasi-experimental research design. The research design is one group pretest and posttest design. The sampling technique used is purposive sampling. The number of samples is 32 respondents. The analysis in this study used the Mc Nemarc test statistical test with a significance level of 95% (α 0.05). The results obtained before the Counter pressure massage was 21.8% who experienced mild pain, after being given Counter pressure there was an increase of 71.8% who experienced mild pain. Based on the Mc Nemarc test, the value of = 0.000 < 0.05, then Ha is accepted and Ho is rejected. Which means that there is an effect of countepressure massage on decreasing pain intensity in maternity mothers during the first active phase. Conclusion of this researchnamely counter pressure massage is effective for reducing the intensity of pain in the first stage of the active phase in maternitybecause it's so focused at the point of pain, Thenexpected midwifein providing caremidwifery can apply counter pressure massage to reduce pain intensity in maternity mothers.